2011
DOI: 10.1111/j.1600-0722.2011.00853.x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-doped dentin adhesive for collagen protection at the hybrid layer

Abstract: The aim of the study was to ascertain whether the addition of zinc to adhesives may decrease metalloproteinase-mediated collagen degradation without affecting bonding efficacy. Human dentin beams were treated with phosphoric acid, with Clearfil SE Bond Primer or with Clearfil SE Bond Primer plus ZnCl(2) (2 wt%). Acid-etched dentin was infiltrated with Single Bond, Single Bond plus ZnCl(2) (2 wt%), or Single Bond plus ZnO nanoparticles (10 wt%), and Clearfil SE Bond-primed dentin was infiltrated with Clearfil S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
78
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 41 publications
5
78
0
2
Order By: Relevance
“…Zinc has been demonstrated to reduce MMPs-mediated collagen degradation (Osorio et al, 2011), to inhibit dentin demineralization (Takatsuka et al, 2005) and to induce dentin remineralization at the bonded interface (Toledano et al, 2013a). Zinc influences signaling pathways and stimulates a metabolic effect in hard tissue mineralization (Hoppe et al, 2011) and remineralization processes (Barcellos et al, 2016;Lynch et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Zinc has been demonstrated to reduce MMPs-mediated collagen degradation (Osorio et al, 2011), to inhibit dentin demineralization (Takatsuka et al, 2005) and to induce dentin remineralization at the bonded interface (Toledano et al, 2013a). Zinc influences signaling pathways and stimulates a metabolic effect in hard tissue mineralization (Hoppe et al, 2011) and remineralization processes (Barcellos et al, 2016;Lynch et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Zn ++ may causes interaction with MDP forming Zn-MDP complexes when it is combined with the primer (SEB·P-Zn doped) and applied on dentin previous to the adhesive bonding placement (SEB·Bd). This reduced the Ca-MDP salts formation (Osorio et al, 2011). As a consequence, the penetration of free MDP into the partially demineralized dentin is compromised, due to simultaneous formation of MDP-Zn and Ca-MDP-Zn salts rather than MDP-Ca (Feitosa et al, 2014).…”
Section: Zn-doped Self-etching Adhesivesmentioning
confidence: 99%
“…These Ca-MDP complexes, organized in nano-layering (Yoshida et al, 2012) did not hamper the inward diffusion of ions. These nano-layers helped for further interactions between the remaining Ca ++ and Zn ++ ions, the curable resin matrix containing acidic functional, Zn-MDP and Ca-MDP-Zn complexes, and the partially demineralized collagen (Osorio et al, 2011). This lower salt formation, plus the alkalinity promoted after mechanical loading (McAllister and Frangos, 1999) could also account for the less effective liberation of zinc ions at the resin-dentin interface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By scanning electron microscope and energy dispersive X-ray analysis of ZnO-doped adhesive bonded dentin surfaces, it was found that ZnO particles penetrate dentinal tubules, but preferentially remained at the bottom of the hybrid layer. They do not penetrate intertubular dentin but remain in direct contact with the demineralized dentin collagen 14 . The deposition of zinc particles at this site will facilitate the effective release of zinc ions and binding to collagen, at the resin-dentin interface.…”
Section: Introductionmentioning
confidence: 99%